Diabetes mellitus and arterial hypertension as a risk factor of mortality in patients with Covid-19 - Navarrete-Mejía, Pedro Javier (2021)
Objetive. to identify the possible association of diabetes mellitus and arterial hypertension as risk factors for mortality in patients with COVID-19. Material and methods: prospective cohort study, includes 1947 patients aged 30 or over, care performed between March and August 2020; patients with clinical and laboratory diagnosis of COVID-19; Patients with inconsistencies in the information recorded, who died in the first 24 hours or were dead on admission, were excluded. Variable period of care, age, sex, diabetes mellitus, arterial hypertension, hospital stay, respiratory rate, heart rate, oxygen saturation and temperature were included; Pearson's chi-square test, Odds Ratio and Student's T test for unpaired samples (p <0.05) were used for the analysis. Results: 73% of male deaths (p <0.001), the highest frequency was between 60-79 years of age (54.8%, p <0.001); diabetes as comorbidity in 17% of cases (p = 0.019) and hypertension in 24% (p <0.001). The variables sex (OR 1.5) and the comorbidities diabetes (OR 1.4) and arterial hypertension (OR 1.9) represent risk factors for mortality. Conclusions: diabetes mellitus and arterial hypertension, for the study population, were identified as a risk factor for mortality against COVID-19.